2015
DOI: 10.1149/06801.0687ecst
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Solid Oxide Cell Oxygen Electrodes Under Pressurization

Abstract: The solid oxide cell (SOC) composite oxygen electrodes (La 0.8 Sr 0.2 ) 0.98 MnO 3-δ -Zr 0.84 Y 0.16 O 2-γ (LSM-YSZ) and La 0.6 Sr 0.4 Fe 0.8 Co 0.2 O 3-δ (LSCF) -Ce 0.8 Gd 0.2 O 1.95 (LSCF-GDC) were studied at oxygen partial pressure pO 2 from 0.1 to 10 atm by impedance spectroscopy. Both electrodes showed a main response at frequency < 100 Hz that decreased in size and frequency with increasing pO 2 , and a smaller response at ~ 10 3 Hz. The impedance spectra were fit using an equivalent circuit model with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…5D whether the oxygen-electrode process at 600 Hz was affected by pressure, but it is assumed that the related resistance also decreases with increasing pressure, as observed in previous pressurized electrode experiments. [23,29] The difference spectrum in Fig. 5B for the shift in the H2O composition has a peak around 6 kHz in agreement with previous observations on Ni-YSZ-electrodes.…”
Section: Impedance Vs Pressuresupporting
confidence: 90%
See 2 more Smart Citations
“…5D whether the oxygen-electrode process at 600 Hz was affected by pressure, but it is assumed that the related resistance also decreases with increasing pressure, as observed in previous pressurized electrode experiments. [23,29] The difference spectrum in Fig. 5B for the shift in the H2O composition has a peak around 6 kHz in agreement with previous observations on Ni-YSZ-electrodes.…”
Section: Impedance Vs Pressuresupporting
confidence: 90%
“…It has previously been observed that charge transfer limited reactions involving dissociative adsorbed oxygen at low coverage on composite LSM/YSZ-electrodes exhibit a -0.25 exponent [23]. The total pressure dependency of an LSM/YSZ electrode was recently reported to exhibit a -0.17 exponent dependency [29]. A -0.27 exponent behaviour have been found for the PH2O dependence for Ni-YSZ electrodes.…”
Section: Impedance Vs Pressurementioning
confidence: 91%
See 1 more Smart Citation
“…The evolution of the impedance diagrams at OCP are given in Fig 7a and 7b for oxygen partial pressures ranging from 0.1 to 1 atm. It can be noticed that the electrode polarization resistance significantly decreases when increasing the oxygen content, as already experimentally observed in [49,74,75]. The reaction order m was estimated fitting the experimental data with the following relation:…”
Section: Experimental Results and Model Validation 41 Electrode 3d Reconstructions And Electrochemical Characterizationsmentioning
confidence: 75%
“…10 Furthermore, previous studies have shown that with increasing the pressure, the total area specific resistance (ASR total ) decreases significantly with fuel electrode supported cells. [11][12][13][14][15] During co-electrolysis operation H 2 O and CO 2 reduction occur at the fuel electrode and require energy supply due to the endothermic properties of the reactions shown in Eqs. 1…”
Section: Asr Polmentioning
confidence: 99%